Effect of the Formulation on the Bioequivalence of Meloxicam: Tablet and Suspension - Helmy, S. A.; El Bedaiwy, H. M. (Drug Research, 2013)
Meloxicam is a non-steroidal anti-inflammatory drug of the enolic acid class that preferentially inhibits cyclooxygenase-2 imparting analgesic, antipyretic and anti-inflammatory effects. This study was conducted to evaluate the effect of formulation on the pharmacokinetics (PK) and comparative bioavailability of suspension (reference) and tablet (test) formulations of meloxicam. In this in vivo study was established according to a single-center, randomized, single-dose, laboratory-blinded, 2 way, cross-over study with a washout period of 2 weeks. Under fasting conditions, 24 healthy Egyptian male volunteers were randomly allocated to receive a single oral dose of 15 mg meloxicam either as 10 mL of a marketed suspension or one tablet. Plasma samples were obtained over a 96-h interval and analyzed for meloxicam by reversed phase liquid chromatography with ultraviolet detection. A non-compartmental model was used to determine the PK parameters of meloxicam. The 90% confidence intervals for the ratio of log transformed values of Cmax, AUC0-t, and AUCt-∞ of the 2 treatments were within the acceptable range (0.8–1.25) for bioequivalence. From PK perspectives, in this small study in healthy Egyptian adult male volunteers, a single 15 mg dose of the tablet formulation was bioequivalent to a single 15 mg dose of the suspension formulation with no significant effect of formulation based on the US FDA’s regulatory definition. No adverse events occurred or were reported during the study and both formulations were well tolerated.
Keywords: meloxicam; pharmacokinetics; bioavailability; ultraviolet; HPLC